Potential Cytotoxic activity of Ganoderma lucidum Extracts on Human Skin Squamous Carcinoma Cell Line - Mahmud, Hala Mohammed; Obaid, Hind Hussein (Iraqi Journal of Science, 2025)
The central focus of this investigation is examining the cytotoxic properties of various crude extracts derived from Ganoderma lucidum (G. lucidum) on human skin squamous carcinoma cells in vitro. The present study centres on three distinct extracts, namely, hot aqueous, cold aqueous, and ethanolic, all of which were prepared from G. lucidum sourced from DXN Company. The primary objective is to elucidate the potential inhibitory effects these extracts have on the proliferation of human skin squamous carcinoma cells. To achieve this goal, the extracts were subjected to analysis using GC-MS technology. The colorimetric assay method also played a critical role in assessing cytotoxicity (inhibition rate) and cellular proliferation (proliferation rate). The study involved preparing eleven dilute solutions in a two-fold series, resulting in concentrations ranging from 7.8 to 4000 μg/ml, which were then applied to the skin squamous carcinoma cell line (passage 27) over 24, 48, and 72 hours. The analysis revealed that G. lucidum predominantly contains organic compounds like alcohols, aldehydes, esters, and ketones. The cytotoxic impacts observed in the skin squamous carcinoma cell line were significantly influenced by the type of extract, its concentration, and the exposure time. Specifically, the higher concentrations (4000 μg/ml) of all three extracts demonstrated a significant inhibition (P≤ 0.05) of cancer cell growth in comparison to the control group (100% viability). Conversely, lower concentrations (7.8-26.5 μg/ml) were found to significantly stimulate (P≤ 0.05) the proliferation of skin cancer cells when compared with the control (viability 100%). The identification and assessment of bioactive compounds in the three G. lucidum extracts suggest these extracts have the potential to inhibit the growth of skin cancer cells.